2018
DOI: 10.1002/adma.201802781
|View full text |Cite
|
Sign up to set email alerts
|

Film Flip and Transfer Process to Enhance Light Harvesting in Ultrathin Absorber Films on Specular Back‐Reflectors

Abstract: Optical interference is used to enhance light-matter interaction and harvest broadband light in ultrathin semiconductor absorber films on specular back-reflectors. However, the high-temperature processing in oxygen atmosphere required for oxide absorbers often degrades metallic back-reflectors and their specular reflectance. In order to overcome this problem, a newly developed film flip and transfer process is presented that enables high-temperature processing without degradation of the metallic back-reflector… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
0
14
1
Order By: Relevance
“…Another study employing 4D electron energy loss spectroscopy suggested that a measured ≈3 ps signal was a signature of electron–hole recombination after a ligand field (LF or d–d) excitation . An ≈3 ps lifetime for all photogenerated carriers would, however, be inconsistent with reported quantum efficiencies of hematite photoanodes as well as reported collection lengths in photoelectrochemical measurements . A more probable cause for the ≈3 ps lifetime is carrier localization, which has been previously suggested to occur in either polaronic or mid‐gap states after LMCT excitation.…”
Section: Resultsmentioning
confidence: 94%
“…Another study employing 4D electron energy loss spectroscopy suggested that a measured ≈3 ps signal was a signature of electron–hole recombination after a ligand field (LF or d–d) excitation . An ≈3 ps lifetime for all photogenerated carriers would, however, be inconsistent with reported quantum efficiencies of hematite photoanodes as well as reported collection lengths in photoelectrochemical measurements . A more probable cause for the ≈3 ps lifetime is carrier localization, which has been previously suggested to occur in either polaronic or mid‐gap states after LMCT excitation.…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, the specular reflectivity of the bottom mirror can be diminished during this annealing step. Recently, a film flip and transfer process was adopted to enable the deposition of bottom mirror after the annealing process . This process has been schematically depicted in Figure a.…”
Section: Light Trapping Schemesmentioning
confidence: 99%
“…a) The steps to fabricate Hematite based MOS cavity, b,c) the reflection spectra for MS cavities with different Hematite layer thicknesses, and d,e) the photocurrent values of the photoanode for different semiconductor layer thicknesses and doping conditions. Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: Light Trapping Schemesmentioning
confidence: 99%
“…It is essential to develop a transfer technique that isolates the bottom layers from the annealing process. Recently, Kay et al developed a film flip and transfer process to make the coating of the metal layer after the annealing step [89], as shown in Figure 6(a). In addition to improving the electrical properties of the layer, the layer is homogeneously doped using Ti.…”
Section: Photoelectrochemical Water Splittingmentioning
confidence: 99%